SELF-ASSESSMENT OF COMMUNICATION SKILLS BY MANAGEMENT STUDENTS: AN EMPIRICAL STUDY IN INDIAN CONTEXT - Kajal Srivastava (University of Kuningan, 2018)
Communication skills are most sought after by the business world and are considered to be vital for personal and professional growth. There have been many researches on the importance of communication skills and how they act as catalysts in getting a job or a dream job. Furthermore, employers, institutes and universities also emphasise that an individual apt at communication skills is more likely to get a job in comparison to one who is not. This study is meant to decipher the communication skills of management trainees at the time of joining the institute through a self-appraisal questionnaire. The research design employed was Descriptive Cross-Sectional. 125 students were chosen from five management institutes in Lucknow(India) by employing non-random Convenience Sampling. Findings indicated that there is an overall fear of public speaking,respondents fall short of words while writing in Englishand need to be encouraged to read more English magazines and novels.Conclusively, a curriculum may be designed wherein the faculty, along with inputs of the students can build a framework with a view to maximising public speaking activities, and other activities may focus upon reading and writing. Moreover, peer-feedback is recommended to enhance reflective learning.Keywords:management students, active listening skills, oral communication skills, communication building strategies, public speaking